Biosorption of Toxic Reactive Blue Textile Dye from Effluent Water Using Immobilized Biomass Based Adsorbent: 10.32526/ennrj/22/20230192 - Sundararaman, Tanjore Ramachandran; Sivalingam, Sivamani; Mabel, Melvin Millicent; Gobinath, Trisha (Environment and Natural Resources Journal, 2024)
The present research employed immobilized Canna indica beads (CIBs) to obtain maximum degradation of highly toxic Reactive Blue Dye (RBD), predominantly used in textile industry. The CIBs were characterized using FTIR and SEM-EDX analysis. A batch adsorption study was conducted to measure the removal of harmful RBD dye. Different factors were examined in the biosorption technique to achieve the maximum level of toxic dye elimination, such as adsorbent-solute interaction time (5-120 min), solution pH (2-10), adsorbent dose (25 to 250 mg/100 mL), RBD concentration (50-250 mg/L), and temperature (30-60°C). Removal of 99.96% of RBD was successfully achieved at the optimum pH 7, RBD concentration of 50 mg/L, adsorbent dosage of 150 mg/100 mL, a temperature of 303 K, and 60 min of interaction time. The Langmuir isotherm and pseudo-second-order (PSO) kinetic model data have been found to be an ideal match compared to the Freundlich isotherm and pseudo-first-order (PFO) kinetic model. The maximum adsorption capacity onto CIBs biosorbent was found to be 70.49 mg/g. It was noticed that the chemical reaction occurred naturally and released heat during the process which denoted an exothermic reaction. These results shown that the adsorption of RBD removal is efficient using prepared adsorbent from Canna indica root tubers. Therefore, these CIBs could be used for other toxic dyes and heavy metals from industrial wastewater.